Pengaruh Penggunaan Knee Decker Terhadap Nyeri Lutut Pada Pengayuh Becak Di Pasar Klewer - Cica Trimandasari; Prasetyo Catur Utomo; Muh Syaiful Akbar (Jurnal Keterapian Fisik, 2018)
Abstract : Elastic Knee Decker, Rickshaw Peddlers, Knee Pain. Knee pain is a sore knee pain in the knee joint that can be known by everyone of all ages. Most of the illnesses can be at home, there are some conditions that require medical, such as surgery or which can cause prolonged illness, damage to the joints, and severe defects if not damaged. The purpose of this study is to find out how effective the decrease of pain in the use of elastic knee decker on pedicab driver in klewer market Surakarta.This type of research is experimental with one group pretest-podt test design, where there is only one group of conscientious subjects to be observed. In this study 20 respondents were given treatment in the form of use of elastic knee decker tool for 20 days. The results of this study indicate that there is an effect of the use of knee decker to decrease the degree of pain in pedicab drivers in the market klewer, with the results of analysis value p = 0,000 (p <0.05), z = -4.041a. The conclusions of this study indicate that the use of elastic knee decker has an influence in decreasing the degree of knee pain in rickshaw peddlers in the market klewer Surakarta.